High in Fiber, Low in Content: Reflections on Postmodern Anthropology - Stoller, Paul (Culture, 1991)
This paper is a critical reflection of the important debate on postmodernism in Anthropology. In the paper, the discourse and counterdiscourses on postmodernism are outlined and assessed. In the end the author (1) worries about plethora of obfuscating criticism and the dearth of revelatory ethnography in the postmodern debate and (2) suggests three paths to a future anthropology beyond the postmodern: sensorial anthropology, ethnographic film, and narrative ethnography.